H5N1 avian influenza virus: an overview - Proença-Módena,José Luiz (2007)
Avian influenza virus (H5N1) emerged in Hong Kong in 1997, causing severe human disease. In recent years, several outbreaks have been reported in different parts of Asia, Europe and Africa, raising concerns of dissemination of a new and highly lethal influenza pandemic. Although H5N1 has not been capable of sustaining human-to-human transmission, the ability of the virus to undergo variation due to mutations and reassortment, clearly poses the possibility of viral adaptation to the human species. For this reason the World Health Organization has established that we are now in a phase of pandemic alert. Preparing for an influenza pandemic involves a great deal of awareness necessary to stop initial outbreaks, through the use of case recognition, sensitive and rapid diagnostic methods, appropriate therapeutic and preventive measures to reduce spread. Influenza pandemic preparedness involves coordinated pharmacologic and vaccinal strategies, as well as containment measures such as travel restrictions and quarantine approaches.